Lipidome Remodeling and Autophagic Respose in the Arachidonic-Acid-Rich Microalga Lobosphaera incisa Under Nitrogen and Phosphorous Deprivation - Kokabi, Kamilya; Gorelova, Olga; Zorin, Boris; Didi-Cohen, Shoshana; Itkin, Maxim; Malitsky, Sergey; Solovchenko, Alexei; Boussiba, Sammy; Khozin-Goldberg, Inna (Frontiers in Plant Science, 2020)
The green microalga Lobosphaera incisa accumulates triacylglycerols (TAGs) with exceptionally high levels of long-chain polyunsaturated fatty acid (LC-PUFA) arachidonic acid (ARA) under nitrogen (N) deprivation. Phosphorous (P) deprivation induces milder changes in fatty acid composition, cell ultrastructure, and growth performance. We hypothesized that the resource-demanding biosynthesis and sequestration of ARA-rich TAG in lipid droplets (LDs) are associated with the enhancement of catabolic processes, including membrane lipid turnover and autophagic activity. Although this work focuses mainly on N deprivation, a comparative analysis of N and P deprivation responses is included. The results of lipidomic profiling showed a differential impact of N and P deprivation on the reorganization of glycerolipids. The formation of TAG under N deprivation was associated with the enhanced breakdown of chloroplast glycerolipids and the formation of lyso-lipids. N-deprived cells displayed a profound reorganization of cell ultrastructure, including internalization of cellular material into autophagic vacuoles, concomitant with the formation of LDs, while P-deprived cells showed better cellular ultrastructural integrity. The expression of the hallmark autophagy protein ATG8 and the major lipid droplet protein (MLDP) genes were coordinately upregulated, but to different extents under either N or P deprivation. The expression of the Δ5-desaturase gene, involved in the final step of ARA biosynthesis, was coordinated with ATG8 and MLDP, exclusively under N deprivation. Concanamycin A, the inhibitor of vacuolar proteolysis and autophagic flux, suppressed growth and enhanced levels of ATG8 and TAG in N-replete cells. The proportions of ARA in TAG decreased with a concomitant increase in oleic acid under both N-replete and N-deprived conditions. The photosynthetic apparatus’s recovery from N deprivation was impaired in the presence of the inhibitor, along with the delayed LD degradation. The GFP-ATG8 processing assay showed the release of free GFP in N-replete and N-deprived cells, supporting the existence of autophagic flux. This study provides the first insight into the homeostatic role of autophagy in L. incisa and points to a possible metabolic link between autophagy and ARA-rich TAG biosynthesis.